Productive infection of human embryonic stem cell-derived NKX2.1+ respiratory progenitors with human rhinovirus - Jenny, R.A.; Hirst, C.; Lim, S.M.; Goulburn, A.L.; Micallef, S.J.; Labonne, T.; Kicic, Anthony; Ling, K.M.; Stick, S.M.; Ng, E.S.; Trounson, A.; Giudice, A.; et al. (ALPHAMED PRESS, 2015)
© AlphaMed Press 2015. Airway epithelial cells generated from pluripotent stem cells (PSCs) represent a resource for research into a variety of human respiratory conditions, including those resulting from infection with common human pathogens. Using an NKX2.1-GFP reporter humanembryonic stem cell line, wede-veloped a serum-free protocol for the generation of NKX2.1 < sup > + < /sup > endoderm that, when transplanted into immunodeficient mice, matured into respiratory cell types identified by expression of CC10, MUC5AC, and surfactant proteins. Gene profiling experiments indicated that day 10 NKX2.1 < sup > + < /sup > endo-derm expressed markers indicative of early foregut but lacked genes associated with later stages of respiratory epithelial cell differentiation. Nevertheless, NKX2.1 < sup > + < /sup > endoderm supported the infection and replication of the common respiratory pathogen human rhinovirus HRV1b. Moreover, NKX2.1 < sup > + < /sup > endoderm upregulated expression of IL-6, IL-8, and IL-1B in response to infection, a characteristic of human airway epithelial cells. Our experiments provide proof of principle for the use of PSC-derived respiratory epithelial cells in the study of cell-virus interactions.